Adaptation, rationality, and advancement: ethnic Albanian organized crime in New York City - Arsovska, Jana (Crime, law and social change, 2016)
The objective of this research is to understand the expansion and advancement of ethnic Albanian organized crime groups in New York City. Many European law enforcement agencies have depicted Albanian organized crime groups as dangerous due to their ability to overcome obstacles, their propensity to use violence, and also because they have progressed from simple service providers to working within the highest echelons of international organized crime. This research examines whether Albanian organized crime groups in New York City have developed more stable structures through the strategic acquisition of information. The article tries to answer: Do Albanian organized crime groups in New York have a long-term strategy for advancement? Are they more risk-seeking and irrational than other organized crime offenders, or are they more risk-averse and rational? Are they malleable learning organizations? This study takes both a thematic and chronological approach, and examines the process of change across four key areas (structure of the criminal organizations; criminal activities; violence; and infiltration and corruption) and over three time periods (1975-1991; 1992-2002; 2003-2014). The conclusions are based on content analysis of court files and official government documents as well as interviews with law enforcement officials and Albanian organized crime offenders, inside and outside of U.S. Federal Prisons.